KONSEP KAFA’AH DALAM PERNIKAHAN MENURUT ISLAM - Siti Fatimah (LPPM STAI DARUSSALAM LAMPUNG, 2014)
Marri a geis a way chosenby Godas away forhumansto breedandthe preservation fhis life, aftereach pairhad beenready to dotherolein realizingthe purpose of marriage. The purpose ofmarriageis the creation ofa familythat is Sakinah, which covered mawadah warahmah. Many ways can be doneto realize the purpose of marriage, one way todetermine. The prospective husband and wifeare good can didate is the concept kafa'ah. But the way is not akey, but most can not determine whether or not the family in later life. Problems kafa'ah actually there and a debate among scholarssect, opinion among the Hanafi school is more about kafa'ah discussin detail other thans chool, because the suspectaccording to the Hanafi school because cosmopolite kafa'ah born people living in Iraq, from diverse social backgrounds so that the Hanafi school considers importantin terms ofsocial kafa'ah (Sosial Equelity). kafa'ah theory those becomes inevitable. As with the Maliki school that develop din the Hijaz and Medina were not important kafa'ah in terms ofsocial, religious and only put forward in choosing a husband and wife. Shafi’i and Hanbali found the kafa'ah flexibleor are presentin adapted local customs. Kafa'ah influencerelation to the purpose of marriage, it turns out this kafa'ah segnifikan has influence with the achievement of the purpose of marriage, bothin terms of religion kafa'ah (Religious Equelity) and insocial terms (Sosial Equelity).